Urban–rural disparities in minimum acceptable diet intake among children aged 6–23 months in Ethiopia: A multivariable Decomposition analysis of Ethiopian demographic and health survey 2019 - Mohammed, Anissa; Tareke, Abiyu Abadi; Keleb, Awoke; Kebede, Natnael; Tsega, Yawkal; Endawkie, Abel; Kebede, Shimels Derso; Mesfin Abera, Kaleab; Tilahun Abeje, Eyob; Bekele Enyew, Ermias; Daba, Chala; Asmare, Lakew; et al. (Frontiers in Public Health, 2024)
Introduction The achievement of the minimum acceptable diet intake (MAD) stands at 14% among urban and 10% among rural under-five children in Ethiopia. Consequently, identifying the determinants of the urban–rural gap is vital for advancing Sustainable Development Goals (SDGs), fostering healthier communities, and developing evidence-driven approaches to enhance health outcomes and address disparities. Objective The objective of the study was to decompose the urban–rural disparities in minimum acceptable diet intake in Ethiopia using the Ethiopian Mini-Demographic and Health Survey 2019 data. Method The study was conducted using the Ethiopian Demographic and Health Survey 2019 report. A total of 1,496 weighted children aged 6–23 months were included using stratified sampling techniques. The main outcome variable minimum acceptable diet was calculated as a combined proportion of minimum dietary diversity and minimum meal frequency. A decomposition analysis was used to analyze the factors associated with the urban–rural discrepancy of minimum acceptable diet intake, and the results were presented using tables and figures. Result The magnitude of minimum acceptable diet among children aged 6–23 months in Ethiopia was 11.0%. There has been a significant disparity in the intake of minimum acceptable diet between urban and rural under-five children with 14 and 10%, respectively. Endowment factors were responsible for 70.2% of the discrepancy, followed by 45.1% with behavioral coefficients. Educational status of college and above was responsible for narrowing the gap between urban and rural residents by 23.9% (β = 0.1313, 95% CI: 0.0332–0.245). The number of children in the household and the age of the child between 18 and 23 months were responsible for widening the gap in minimum acceptable diet intake discrepancy between urban and rural residents by 30.7% and 3.36%, respectively (β = −0.002, 95% CI: −0.003 to −0.0011 and β = −30.7, 95% CI: −0.025 – −0.0085). From the effect coefficients, the effect of institutional delivery was responsible for 1.99% of the widening of the gap between urban and rural residents in minimum acceptable diet intake (β = −0.0862, 95% CI: −0.1711 – −0.0012). Conclusion There is a significant variation between urban and rural residents in minimum acceptable diet. The larger portion of the discrepancy was explained by the endowment effect. Educational status of mothers with college and above, parity, age of child, and place of delivery were the significant factors contributing to the discrepancy of minimum acceptable diet intake between urban and rural residents.